ASSESSMENT OF BACTERIA ASSOCIATED WITH FINGER NAILS SOME PRIMARY SCHOOL PUPILS IN DUTSIN MA METROPOLIS, KATSINA STATE, NIGERIA - Eberemu, Nkiru; Magu, J. T. (FUDMA Journal of Sciences, 2023)
This study was conducted to access bacteria under the nails of primary school pupils in Dutsin Ma Metropolis, Katsina State, Nigeria. Samples were by means of sterile cotton swabs moistened in 0.85g physiological saline from 200 pupils in four different schools and were identified by culture and biochemically characterized in Biology Laboratory, Federal University Dutsin Ma. The result indicated that 198 samples were found to habour bacteria under the finger nails. Bacterial pathogens isolated from the under nails of the pupils included Staphylococcu spps which had the highest prevalence of 74(37%) followed by Escherichia coli with prevalence of 61(30%) while Proteus spp and Klebsiella spp had 21(10.5%) and 16(8%) respectively. Pseudomonas spp had 10(5%) and the least was Salmonella spp which had a prevalence of 7(3.5%). The highest prevalence of bacteria isolates were seen in male pupils with 31 while the female pupilswere 18 isolates more number of bacteria isolates was also observed in pupils of age group 5-7years. Through basic hygiene, these bacteria contamination can be minimized
Keywords: Finger nails, Bacteria, Pupils